Targeting the crosstalk between cytokine-induced killer cells and myeloid-derived suppressor cells in hepatocellular carcinoma - Yu, Su Jong (J Hepatol, 2018)
BACKGROUND: Cytokine-induced killer (CIK) cell-based immunotherapy is effective as adjuvant therapy in early stage hepatocellular carcinoma (HCC) but lacks efficacy in advanced HCC. We investigated immune suppressor mechanisms focuing on CIKs and myeloid-derived suppressor cells (MDSCs). METHODS: MDSCs were quantified by flow cytometry and quantitative real-time PCR. Cytokines were detected by cytokine array. An LDH cytotoxicity assay was performed in the presence or absence of MDSCs to study CIK function against HCC cells in vitro. An FDA approved PDE5 inhibitor, tadalafil, was used to target MDSCs in vitro and in vivo. Two different murine HCC cell lines were tested in subcutaneous and orthotopic tumor models in C57BL/6 and BALB/c mice. The anti-tumor effects of human CIKs and MDSCs were also tested in vitro. RESULTS: Adoptive cell transfer of CIKs into tumor bearing mice induced inflammatory mediators (e.g., CX3CL1, IL-13) in the tumor microenvironment and an increase of tumor infiltrating MDSCs leading to impaired anti-tumor activity in two different HCC tumor models. MDSCs efficiently suppressed the cytotoxic activity of CIKs in vitro. In contrast, treatment with a PDE5 inhibitor reversed the MDSC suppressor function via ARG1 and iNOS blockade and systemic treatment with a PDE5 inhibitor prevented MDSC accumulation in the tumor microenvironment upon CIK cell therapy and increased its anti-tumor efficacy. Similar results were observed when human CIKs were tested in vitro in the presence of CD14(+)HLA-DR(−/low) MDSCs. Treatment of MDSCs with a PDE5 inhibitor suppressed MDSCs suppressor function and enhanced CIK activity against human HCC cell lines in vitro. CONCLUSION: Our results suggest that targeting MDSCs is an efficient strategy to enhance the antitumor efficacy of CIKs for the treatment of patients with HCC.